Limites da negociação coletiva para proteção dos direitos fundamentais dos trabalhadores - Machado, Anna Catharina Fraga (2014)
The Federal Constitution of 1988 established a long list of rights and guarantees minimum standards for worker protection, to comply with the fundamentals of the Brazilian Federative Republic, embodied in the scope of human dignity and social value of the work. In this sense it is objective of labor law, by establishing principles and rules protective of working relationship, enable achievement of decent conditions for workers, especially in view of the employee be subject hipossuficiente the employment relationship. It is well to see that in the meantime so delicate relationship, collective negotiation arises as a mechanism to promote dialogue and provide adjustment of the different interests involved, since it has ductile nature to obtain optimal solutions, and should establish social bases minimum for good living and well being of the characters of the capital/labor ratio, the prospect that they contribute as partners in the economic development of the country. Collective negociation (and its possible fruits Conventions and Collective Negociation Agreements) should be through enforcement of the fundamental rights of workers. There is no other reason that the International Labour Organization recommends that collective bargaining is a fundamental right essential to the exercise of democracy and social dialogue. In the parental right to attempt collective bargaining is mandatory and must precede the collective bargaining agreement, according predicts Article 114, §§ 1st and 2nd, CF/88. However, important to note that collective bargaining can not result in undue benefits designed to meet unique interests of certain unions, to the detriment of the fundamental rights of workers. In this vein, the CF/88 while recognizing the institution of collective negociation as a fundamental right (item XXVI), establishes some parameters of what can be its object. So it is that in items of art. 7 of the Charter Biggest predicts that the wages (section VI) and workload (sections XIII and XIV) can be modified within the scope of collective negociation. Importantly, however, in everyday life we observe the existence of collective norms that deviate from the essence that should guide collective negociation. Therefore highly relevant research regarding its limits, through the possibility of cancellation of unfair terms, thus raising the debate with regard to the availability of workers´ rights at collective negociation´s headquarters.